2022
DOI: 10.1016/j.jvoice.2020.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Telemedicine in a Laryngology Practice During the COVID-19 Pandemic: Lessons Learned, Experiences Shared

Abstract: Objectives. The novel coronavirus disease 2019 has posed significant limitations and barriers to providing in-person healthcare. We aim to provide a summary of learned experiences and important considerations for implementing and offering telehealth to provide laryngology subspecialty care during the COVID-19 pandemic and thereafter. Materials and Methods. Four laryngologists and a voice-specialized speech-language pathologist from a tertiary-care academic Voice and Swallowing Center were engaged in a structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 26 publications
(37 reference statements)
3
38
0
Order By: Relevance
“…Specialties that focus on children or require medical equipment (eg, otorhinolaryngology or ophthalmology) experienced the highest reduction of in-person visits. This is consistent with recent studies that identified a lack of access to laryngoscopes as a downside of telemedicine visits [ 20 ]. Even though telemedicine has provided physicians with an option to deliver outpatient services, the recovery of outpatient clinical activity levels toward 2019 levels differed between specialty groups.…”
Section: Discussionsupporting
confidence: 93%
“…Specialties that focus on children or require medical equipment (eg, otorhinolaryngology or ophthalmology) experienced the highest reduction of in-person visits. This is consistent with recent studies that identified a lack of access to laryngoscopes as a downside of telemedicine visits [ 20 ]. Even though telemedicine has provided physicians with an option to deliver outpatient services, the recovery of outpatient clinical activity levels toward 2019 levels differed between specialty groups.…”
Section: Discussionsupporting
confidence: 93%
“…Video‐enabled telemedicine can provide helpful preliminary information such as global swallowing function and change in voice quality/aspiration symptoms after swallow. 24 However, accurate diagnosis often requires additional assessments including laryngoscopy along with modified barium swallow study, CT or MRI. Conservative management with acceptable benefit‐to‐risk ratios was often recommended empirically including dietary and behavioral management of reflux, proton pump inhibitors, H2‐blockers, alginates, antibiotics, and steroids based on appropriate history and preliminary diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Across 172 completed screenings, 110 patient needs were identified of which 21% (36) were psychosocial/practical, 10% (17) were nutritional, 11% (19) were related to anxiety, 9% (16) were related to physical function, 6% (10) were related to depression, 4% (7) were related to pain interference, and 3% (5) were related to fatigue (Table 2). Across all domains, a higher percentage of patients screened telephonically reported symptoms severe enough to trigger an alert when compared to those who completed the screener on their own through MyChart, as seen in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 The onset of the COVID-19 pandemic required rapid responses to changing in-clinic workflows and a shift to increased telehealth visits. Strohl et al 19 suggest telemedicine carries limitations in the ability to conduct a thorough physical exam and other investigations. Capturing data is of utmost importance during a telemedicine visit, particularly during the pandemic when the ability to capture PROMs during in-person clinic visits was limited.…”
mentioning
confidence: 99%